2013
DOI: 10.1080/07060661.2013.763293
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of clubroot development and management on canola and Brassica vegetables

Abstract: A comparison of clubroot development and management on canola and Brassica vegetables, Canadian Journal of Plant Pathology, 35:2, 175-191, Abstract: Clubroot of canola was identified for the first time on the Canadian prairies in 2003, and is spreading rapidly across the region.Although clubroot has been studied extensively on vegetable Brassica crops, it was not clear initially how much of the information would be directly transferable from the intensive production of vegetable crops to the extensive producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 75 publications
0
11
1
Order By: Relevance
“…Increased levels of soil OM have been reported to decrease the severity of clubroot, although conflicting results have been obtained (Gossen et al 2013). However, in the present study, high levels of soil OM were observed (9.65 to 58.44 g/kg soil), with similar mean values for the two groups.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…Increased levels of soil OM have been reported to decrease the severity of clubroot, although conflicting results have been obtained (Gossen et al 2013). However, in the present study, high levels of soil OM were observed (9.65 to 58.44 g/kg soil), with similar mean values for the two groups.…”
Section: Discussioncontrasting
confidence: 60%
“…botrytis L.), bok choy (B. pekinensis L.), broccoli (B. oleracea L. var. As the disease progresses, there is a reduction in the effective root system of the plant and, consequently, a reduction in the water and nutrient absorption process, which leads to the appearance of secondary symptoms, such as wilting during the hottest hours of the day, stunting, and reduced biomass production and commercial quality of the vegetables (Gossen et al 2013). The life cycle of P. brassicae is complex and can be divided into two phases: i) germination of the resting spores under stimulation from root exudates of host species, release of the primary zoospores, and subsequent infection of the root hairs; and ii) colonization and proliferation of the pathogen in the cortex of the roots and subsequent formation of root galls (Niwa et al 2008).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(Tewari et al ., ). By 2007, the pathogen had become established in an extensive region around the initial area of infestation and is considered to be a threat to the entire Canadian canola industry (Strelkov et al ., ; Gossen et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…roots (Usuki & Narisawa 2007). This characteristic may limit the use of traditional rhizosphere-colonizing microorganisms with potential for clubroot management (Gossen et al 2013).…”
Section: Control Typementioning
confidence: 99%